Dormant cells of Staphylococcus aureus are resuscitated by spent culture supernatant. - Ben Pascoe; Lucy Dams; Tom S Wilkinson; Llinos G Harris; Owen Bodger; Dietrich Mack; Angharad P Davies (PLoS ONE)
We describe the first in vitro model of dormancy in Staphylococcus aureus, showing that cells are generated which can be resuscitated by addition of spent medium supernatant taken from cultures of the same organism. Over 30 days, culturable counts in dormant cultures of S. aureus SH1000 fell from 10(6)-10(7) cfu/ml to <10 cfu/ml as measured by the Most Probable Number method in liquid culture, while total counts as determined by microscopy, and supported by data from RT-qPCR, remained around 10(6)-10(7) cells/ml. Supplementing cultures with 25-50% spent medium resulted in a >600-fold increase in bacterial growth. Resuscitation was a specific effect, greatly reduced by boiling or addition of trypsin to the spent supernatant. Supernatant also effected a reduction in lag phase of dormant cultures. SEM demonstrated the presence of small coccoid cells in dormant cultures. The results are similar to those seen with resuscitation promoting factors (Rpfs) in actinobacteria. This is the first time resuscitation has been demonstrated in Staphylococcus aureus, which is an important human pathogen. A better understanding of control and reactivation of dormant cells could lead to major improvements in managing staphylococcal infections; resuscitation could be an important step in restoring susceptibility to antibiotic treatment.